An Effective Thresholding Technique for Otsu’s Method using Contrast Enhancement (International Journal of Engineering and Computer Science, 2017)
Image segmentation is the fundamental approach of digital image processing. Among all the segmentation methods, Otsu method is one of the most successful methods for image thresholding because of its simple calculation. Otsu is an automatic threshold selection region based segmentation method. This paper works based on the principle of binarization of Otsu's method. In addition, various enhancement schemes are used for enhancing an image which includes gray scale manipulation, filtering and Histogram Equalization (HE). Histogram equalization is one of the well-known image enhancement technique. It became a popular technique for contrast enhancement because this method is simple and effective. In the latter case, preserving the input brightness of the image is required to avoid the generation of non-existing artifacts in the output image. Although these methods preserve the input brightness on the output image with a significant contrast enhancement, they may produce images with do not look as natural as the input ones. The proposed work is divided into three stages. Firstly, Histogram Equalization is applied to the low contrast input image. Secondly, we are obtaining the bimodal image by applying Otsu's binarization, Thirdly, Otsu's thresholding technique is applied to get the binary image. The experimental analysis shows that the results are better than the state of the art methods applied. We have shown the comparison results subjectively as well as objectively. Subjective parameters are visual quality and computation time and objective parameters are Peak signal to-noise ratio (PSNR), Mean squared error (MSE and Average Information Content (AIC).